Alteração de cor em dentes artificiais de resina acrílica: Estudo clínico retrospectivo de 5 anos - Ogawa, Erika Shiguematsu [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Although acrylic resin denture teeth have been widely used owing to their chemical bond to denture base acrylic resin and easy wear during occlusal adjustment, color instability is a common complication. Intrinsic and extrinsic factors such as temperature change, humidity, absorption and adsorption of substances can affect the color stability of denture teeth. Therefore, this study investigated, the color alteration of acrylic resin artificial denture teeth in complete dentures users treated at Aracatuba Dental School - UNESP during the last five years. Complete dentures users rehabilitated by undergraduate students of the Complete Denture discipline of this Institution from 2006 to 2011 were selected. The color stability was measured through a spectrophotometer and the color alterations was calculated by the CIE L*a*b* system. A questionnaire was applied to collect some parameters that may affect the color change of the artificial denture teeth of the patients included herein. There were found no statistically significant change for the middle third of the tooth. New statistics will be needed to investigate possible changes in the cervical and incisal thirds

Os dentes de resina acrílica têm sido amplamente utilizados por apresentarem união química com a resina acrílica da base protética e por permitirem fácil desgaste durante o ajuste oclusal, no entanto, apresentam uma maior instabilidade de cor. Fatores intrínsecos e extrínsecos podem contribuir para essa alteração: mudanças de temperatura e umidade, absorção e adsorção de substâncias entre outros. Este estudo teve por objetivo avaliar a alteração de cor dos dentes artificiais de resina acrílica em pacientes usuários de prótese total tratados na Faculdade de Odontologia de Araçatuba - UNESP, nos últimos cinco anos. Foram selecionados pacientes usuários de próteses totais reabilitados pelos alunos de graduação nos anos de 2006 a 2011. O teste de estabilidade de cor foi verificado por meio de um espectrofotômetro com as alterações de cor calculadas através do Sistema CIE L*a*b*. Um questionário foi aplicado para que fosse possível avaliar as possíveis causas de alteração de cor dos dentes artificiais dos pacientes incluídos nessa pesquisa. Não foram encontradas nenhuma alteração estatisticamente signicante para o terço médio do dente. Novas estatísticas serão necessárias para averiguar possíveis alterações nos terços incisal e cervical
Keywords: Prótese total; Cor; Prótese dentária; Denture, Complete